Paths are created by teaching! Educational proposals to the Bicentennial Peru in light of the historia - Benito, José Antonio (2015)
Beyond the memory of independent Peru’s liberation war in 1821, we emphasize one of the keys to understand its historical journey: its rich educational and cultural heritage made from walking, both in its religious pilgrimage and in its educational accomplishments. Therefore, the best way to commemorate the bicentennial will be to know in a thorough way its cultural legacy and to commit ourselves to an inclusive and complrehensive education for all Peruvians.